Diagnosis and Treatment-Spectrum Beta-Lactamase and Multidrug Resistance Bacterial - Liya Anjelina; Armen Ahmad (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Multidrug-resistant (MDR) is a condition resistant to at least one type of antibiotic from 3 classes of antibiotics. Extended-Spectrum Beta Lactamases are globular proteins that consist of alpha-helices and beta-pleated sheets. β-lactamase hydrolyze broad-spectrum cephalosporin with oxyimino side chain. ESBL hydrolyze antibiotics group penicillin, cephalosporin first, second, third, fourth generation, and monobactam aztreonam. Multidrug resistance occurs through two mechanisms, bacteria accumulate multiple genes encoding resistance to one antibiotic, and due to increased expression of genes encoding multidrug effluent pump, enzymatic inactivation and target structure change. Multidrug-resistant (MDR) caused by extended-spectrum resistance beta-lactamase (ESBL) can be detected by phenotyping and genotyping methods. Treatment for MDR ESBLs other than carbapenems can be β-lactam/β-lactamase inhibitor combinations (BLBLIs), namely piperacillin/tazobactam (PZT).